Corpus-Based Research in Vocabulary Learning (Universitas Islam Negeri Sunan Ampel Surabaya, 2020)
n the university, corpus-based research is commonly done for writing a thesis. However, corpus-based research can also be introduced for the first year of EFL students to build their critical thinking and vocabulary mastery. Less research discusses the practice of corpus-based research for the first year EFL student. Therefore, it is essential to investigate the benefit and the challenges of corpus-based research in the Indonesian EFL Setting. This study aims to examine the benefits and the challenges of corpus-based research in the Indonesian EFL Setting. Students did corpus-based research in English for the Islamic Studies course. Students tried to structure an English glossary from online Islamic articles, Islamic journals, and Islamic blogs. Forty-four students were chosen as the subject of the research. The survey was done to the students to gather the data about the benefits and the challenges of corpus-based research. The results showed that corpus-based research benefits increase vocabulary, increase students' understanding of research, improve students' accuracy in writing, develop critical thinking, and develop collaboration. Students faced several challenges in implementing corpus-based research. The finding shows students have difficulties in understanding new vocabulary. Besides, they have problems classifying data into specific topics, allocating time, and writing their reports.